Emoção e aprendizagem de temas ambientais com integração de tecnologias na experiência de estudantes surdos. - Garcia, Gisele Pereira Gama (Universidade Federal Rural do Semi-Árido, 2018)
The research discusses the learning of deaf people in relation to environmental issues. The author analyzes the experiences of students in relation to learning and contact with an environmental theme. The methodology used is qualitative, in the form of research and involved the development of workshops on environmental themes, with emphasis on the concept of semiarid. The analysis is considered as one of the strategies of control of change of conduits in the sessions of interaction between participants that construct the environmental questions. The main components of data collection were: on-board analysis, filming and photographs, conversation wheels, experience analysis, observation and analysis of the productions made in the workshops. We were able to distinguish the actions of people at the service of concepts and in the production directives on environmental policies. Truth and joy were emerging in doing, 9 transforming experience into a journey through fear and mistrust in their perceptual conditions due to deafness. As a result of research, it is also possible to emphasize the need to put into practice building processes, materials, supports for learning of people who are not and do not exercise during the learning process in their training exercises and their knowledge and life paths
Keywords: emoção; aprendizagem; pessoas surdas; temas ambientais; tecnologias; emotion; learning; deaf people; environmental themes; technologies; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE